Asuhan Kebidanan Pada Ibu Nifas Dengan Perawatan Luka Perineum Di Klinik Pratama Medical Center Kota Batam - Sthepani Sari Hidayat; Susanti Susanti (Pusat riset dan Inovasi Nasional, 2024)
The puerperium is a period that will be passed by the mother after the delivery period, which starts after the birth of the baby and placenta, namely after the end of stage IV in labor and ends up to 6 weeks (42 days) which is marked by the cessation of bleeding. The puerperium is a period that is very vulnerable to infection for postpartum mothers if the treatment is not appropriate. Many postpartum mothers do not know how to maintain their hygiene, especially in the genital area. Mothers just clean it without caring about good and correct vulva hygiene, so that wound healing becomes slow (> 6 days). This type of research is descriptive by applying a case study approach. The implementation of this research was carried out at the Pratama Medical Center Clinic for Mrs. N by providing care for the implementation of genital cleansing and perineal wound care.